Photocatalyst, manufacturing method thereof, and decomposition method of water using photocatalyst

The production of ScVO4 composite oxide particles through calcination and flux treatment addresses the inefficiencies of conventional photocatalysts, enabling efficient water decomposition into hydrogen and oxygen, suitable for clean energy and environmental applications.

JP2025008741APending Publication Date: 2025-01-20SUMITOMO METAL MINING CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023111173
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-06
Publication Date
2025-01-20

AI Technical Summary

Technical Problem

Conventional photocatalytic materials, such as vanadium-based compounds, face challenges in efficiently decomposing water into hydrogen and oxygen due to band gap and conduction band positioning, stability issues, and the need for composite catalysts that can effectively utilize visible light for water splitting.

Method used

A method for producing ScVO4 composite oxide particles by calcining a mixture of scandium and vanadium raw materials at high temperatures and treating the reaction product in a flux, followed by alkaline washing and supporting co-catalysts like RhCrOx, to achieve a photocatalyst with improved water splitting performance.

Benefits of technology

The resulting photocatalyst effectively decomposes water into hydrogen and oxygen under ultraviolet light, demonstrating enhanced stability and catalytic activity, suitable for clean energy generation and environmental purification.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025008741000001_ABST
    Figure 2025008741000001_ABST
Patent Text Reader

Abstract

To provide a photocatalyst excellent specifically in water decomposition performance and a manufacturing method thereof, and also to provide a decomposition method of water using the photocatalyst.SOLUTION: A method is for manufacturing a photocatalyst having a composite oxide particle containing ScVO4 as a main component compound. The method includes: a step of mixing scandium (Sc) and vanadium (V) materials to obtain a raw material mixture; a step of burning the raw material mixture at a temperature of 680°C or higher to obtain a reaction product; and a step of heat-treating the reaction product in a flux to obtain a heat-treated reaction product.SELECTED DRAWING: Figure 7B
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a photocatalyst, a method for producing the same, and a method for splitting water using the photocatalyst. [Background technology]

[0002] Due to the problems of global warming and the depletion of fossil fuel resources, technological development related to water splitting reactions using photocatalysts has been attracting attention. By utilizing water splitting reactions, solar energy can be converted into chemical energy such as hydrogen and put to effective use.

[0003] In the photolysis of water using photocatalysts, fine semiconductor particles are dispersed in water and irradiated with light to produce hydrogen and oxygen. When the semiconductor particles absorb light with energy equal to or greater than the band gap of the semiconductor particles, electrons in the valence band are excited to the conduction band. As a result, negatively charged free electrons are generated in the conduction band, and positively charged holes are generated in the valence band. These migrate to the surface of the semiconductor particles, where the holes oxidize water to produce oxygen, and the free electrons reduce hydrogen ions to produce hydrogen.

[0004] To cause the water splitting reaction, the semiconductor particles must be irradiated with light with an energy equal to or greater than the band gap of the semiconductor particles. In other words, the semiconductor particles can only absorb light with an energy greater than their band gap.

[0005] Titanium oxide has been known as a photocatalytic material for some time. However, titanium oxide has a large band gap of 3.0 eV or more, and anatase-type titanium oxide has a low oxygen generation rate. According to Non-Patent Document 1, rutile-type titanium oxide is capable of water splitting when Rh, Pt, or Pd is used as a co-catalyst, but does not exhibit water splitting activity when carrying a RhCrOx catalyst, making it difficult to prevent reverse reactions. Therefore, it is not suitable for high efficiency.

[0006] For this reason, the development of photocatalytic materials other than titanium oxide is progressing, and among them, vanadium-based compounds are attracting attention. For example, vanadium oxide (V2O5) and monoclinic bismuth vanadate (BiVO4) are oxides that have an appropriate band gap (2.3 eV or 2.4 eV) and are known as excellent oxygen-generating photocatalysts. However, because the lower end of the conduction band is more noble than the hydrogen generation level, they are often used as Z-scheme photocatalysts combined with hydrogen generation catalysts rather than as water splitting catalysts.

[0007] As a document related to vanadium-based compounds, Patent Document 1 discloses photocatalyst particles made of BiVO4. Specifically, for a composite photocatalyst including visible light responsive photocatalyst particles for hydrogen generation and visible light responsive photocatalyst particles for oxygen generation, it is described that the visible light responsive photocatalyst particles for oxygen generation are BiVO4 or the like, and that the composite catalyst is used in the photolysis reaction of water by visible light (claims 1 and 9 of Patent Document 1).

[0008] Although it is used for an application other than the water splitting reaction, Patent Document 2 discloses a visible light responsive photocatalyst in which lanthanum (La) is doped into some of the Bi sites of bismuth vanadate (BiVO4) (claim 1 of Patent Document 2). Patent Document 2 describes that, with regard to this photocatalyst, the upper end position of the valence band of BiVO4 is lowered by doping with La, increasing the oxidizing power, and as a result, it becomes possible to improve the decomposition ability of organic matter (

[0008] of Patent Document 2). [Prior art documents] [Patent documents]

[0009] [Patent Document 1] International Publication No. 2014 / 046305 [Patent Document 2] JP 2020-040830 A [Non-patent literature]

[0010] [Non-Patent Document 1] Maeda, Kazuhiko. Photocatalytic properties of rutile TiO2 powder for overall water splitting. Catalysis Science & Technology 4.7 (2014): 1949-1953. Summary of the Invention [Problem to be solved by the invention]

[0011] Thus, although photocatalytic materials made of vanadium-based compounds have been proposed, there is still room for improvement in conventional materials. That is, in order to generate hydrogen by decomposing water, the potential at the bottom of the conduction band of the photocatalytic material must be more base than the hydrogen generation potential. In addition, in order to generate oxygen by decomposing water, the potential at the top of the valence band must be more noble than the oxygen generation potential. Here, the hydrogen generation potential is the potential at which protons in water are reduced to generate hydrogen gas. In addition, the oxygen generation potential is the potential at which water is oxidized to generate oxygen.

[0012] Therefore, in order for a photocatalytic material to absorb light and decompose water, thereby generating both hydrogen and oxygen, it is necessary that the band gap of the photocatalytic material is smaller than the light energy, and further that the conduction band bottom potential is more base than the hydrogen generation potential and the valence band top potential is more noble than the oxygen generation potential.

[0013] In this regard, vanadium oxide (V2O5) has a smaller band gap (2.7 eV) than anatase titanium oxide, but the bottom of the conduction band is on the nobler potential side than the hydrogen generation potential, so excited electrons cannot be used for hydrogen generation. In addition, V2O5 dissolves in water and changes into a colloidal state, so it cannot be used stably in water.

[0014] Although monoclinic BiVO4 has a smaller band gap (2.4 eV) than anatase titanium oxide, the lower end of the conduction band is more noble than the hydrogen generation potential, like V2O5, so electrons cannot be used for hydrogen generation. The composite photocatalyst proposed in Patent Document 1 requires photocatalyst particles for hydrogen generation, such as rhodium-doped strontium titanate, in addition to photocatalyst particles for oxygen generation, such as BiVO4 (claims 1 and 5 of Patent Document 1).

[0015] Furthermore, although Patent Document 2 proposes a photocatalyst made of La-doped BiVO4, this photocatalyst is for decomposing organic matter, not for decomposing water. In fact, Patent Document 2 shows that the electronic energy level at the bottom of the conduction band of La-doped BiVO4 is the same as that of conventional BiVO4 (see

[0044] and Figure 4 of Patent Document 2). Therefore, it is considered that the photocatalyst (La-doped BiVO4) proposed in this document, like conventional BiVO4, cannot reduce hydrogen ions to generate hydrogen.

[0016] Under these circumstances, we discovered that a new vanadium-based compound photocatalyst containing ScVO4 as its main component has a relatively small band gap and is promising as a photocatalyst for water splitting. Some of the inventors then filed a patent application for this photocatalyst (Patent Application No. 2023-030812).

[0017] As a result of further investigations, the inventors discovered that in a method for producing a photocatalyst containing ScVO4 as the main component, a photocatalyst with particularly excellent water splitting performance can be obtained by employing a method in which a raw material mixture is calcined at a prescribed temperature to obtain a reaction product, and then the obtained reaction product is heat-treated in a flux.

[0018] The present invention was completed based on these findings, and an object of the present invention is to provide a photocatalyst that is particularly excellent in water splitting performance and a method for producing the same. Another object of the present invention is to provide a method for splitting water using the photocatalyst. [Means for solving the problem]

[0019] The present invention encompasses the following aspects (1) to (5). In this specification, the expression "to" includes both ends of the expression. In other words, "X to Y" is synonymous with "X or more and Y or less."

[0020] (1) A method for producing a photocatalyst having composite oxide particles containing ScVO4 as a main component compound, comprising the steps of: mixing a scandium (Sc) raw material and a vanadium (V) raw material to obtain a raw material mixture; calcining the raw material mixture at a temperature of 680° C. or higher to obtain a reaction product; and heat treating the reaction product in a flux to obtain a heat-treated reaction product.

[0021] (2) The method according to (1) above, wherein the flux is at least one selected from the group consisting of chlorides, carbonates, and hydroxides of alkali metal elements, and vanadium oxide (V2O5).

[0022] (3) The method according to (2) above, wherein the flux is a mixture of sodium chloride (NaCl) and potassium chloride (KCl).

[0023] (4) A photocatalyst obtained by any one of the methods (1) to (3) above.

[0024] (5) A method for decomposing water, comprising irradiating a suspension containing the photocatalyst of (4) above and water with ultraviolet light, thereby decomposing the water to generate hydrogen and oxygen. Effect of the Invention

[0025] According to the present invention, there are provided a photocatalyst having particularly excellent water splitting performance and a method for producing the same. Also, according to the present invention, there is provided a method for splitting water using the photocatalyst. [Brief description of the drawings]

[0026] [Figure 1] 1 shows an XRD spectrum of the ScVO4 composite oxide particles of Experimental Example 1. [Diagram 2]1 shows an SEM photograph of the ScVO4 composite oxide particles of Experimental Example 1. [Diagram 3] 1 shows an XRD spectrum of the ScVO4 composite oxide particles of Experimental Example 2. [Figure 4] 1 shows an SEM photograph of ScVO4 composite oxide particles of Experimental Example 2. [Diagram 5] 1 shows an XRD spectrum of ScVO4 composite oxide particles of Experimental Example 3. [Figure 6A] 1 shows an SEM photograph of the ScVO4 composite oxide particles of Experimental Example 1. [Figure 6B] 1 shows an SEM photograph of ScVO4 composite oxide particles of Experimental Example 3. [Figure 7A] The results of evaluating the water splitting photocatalytic activity of the ScVO4 composite oxide particles of Experimental Example 1 are shown. [Figure 7B] The results of evaluating the water splitting photocatalytic activity of the ScVO4 composite oxide particles of Experimental Example 3 are shown. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0027] A specific embodiment of the present invention (hereinafter, referred to as the present embodiment) will be described below. However, the present invention is not limited to the following embodiment, and various modifications are possible within the scope of the present invention.

[0028] <<1. Photocatalyst>> The photocatalyst of this embodiment includes composite oxide particles, and the composite oxide particles include scandium vanadate (ScVO4) having a tetragonal crystal structure (zircon structure) as a main component compound. The main component refers to a component that occupies 50 mass% or more in the composite oxide particles. ScVO4 has semiconductor properties, and the band gap calculated by first-principles calculation is relatively small at 2.6 eV. In addition, the conduction band bottom potential in the band structure is at a potential lower than the hydrogen generation potential, and the valence band top potential is at a potential higher than the oxygen generation potential. Therefore, it is considered that the composite oxide particles can absorb light with a wavelength of 480 nm or less and decompose water into hydrogen and oxygen.

[0029] The composite oxide particles do not exclude the inclusion of components other than ScVO4. Such components include heterogeneous phases such as scandium oxide (Sc2O3) and vanadium oxide (V2O5). However, scandium oxide has poor catalytic activity. Vanadium oxide also lacks stability in water. When using a photocatalyst for the water splitting reaction, the photocatalyst needs to come into contact with water, and it is desirable for the photocatalyst to have excellent stability in water.

[0030] The composite oxide particles are not limited in the content ratio of scandium (Sc) and vanadium (V), provided that the composite oxide particles contain ScVO4 as the main component. However, particles containing an excessive amount of scandium contain a large amount of heterophases such as scandium oxide, which has poor catalytic activity. Moreover, an excessive amount of vanadium contains a large amount of heterophases such as vanadium oxide, which has high solubility in water and lacks stability in water. From the viewpoint of ensuring excellent catalytic activity and stability in water, the atomic ratio (V / Sc) is preferably 0.90 to 1.00, more preferably 0.93 to 1.00.

[0031] The atomic ratio (V / Sc) of the composite oxide particles can be controlled by adjusting the conditions during photocatalyst production. For example, the atomic ratio of the final composite oxide particles can be controlled by adjusting the amount of vanadium and scandium raw materials mixed in the raw material mixing process. In addition, excess V2O5 can be removed by subjecting the reaction product obtained by firing to an alkaline washing process.

[0032] The particle size of the composite oxide particles is preferably 0.1 μm or more and 10 μm or less, more preferably 0.3 μm or more and 5 μm or less. Composite oxide particles with an excessively small particle size may have low crystallinity and poor photocatalytic activity. In addition, composite oxide particles with an excessively large particle size may have a small specific surface area and therefore may be difficult to obtain sufficiently high catalytic activity when used in a water splitting reaction. The particle size is determined by measuring SEM images or TEM images.

[0033] Preferably, the photocatalyst further includes a co-catalyst supported on the surface of the composite oxide particles. The co-catalyst is classified into a hydrogen generation co-catalyst, an oxygen generation co-catalyst, and the like. The hydrogen generation co-catalyst mainly has the function of promoting the reduction of hydrogen ions by electrons, and the oxygen generation co-catalyst mainly has the function of promoting the oxidation of water by holes. In particular, by supporting the hydrogen generation co-catalyst on the surface of the photocatalyst made of semiconductor particles, it is possible to dramatically improve the water splitting performance.

[0034] As the material of the promoter, a material such as a known metal or compound may be selected. As such a material, at least one metal selected from the group consisting of platinum (Pt), gold (Au), silver (Ag), iridium (Ir), rhodium (Rh), ruthenium (Ru), cobalt (Co), nickel (Ni), chromium (Cr), and iron (Fe), or one or more selected from the group consisting of oxide particles such as ruthenium oxide and nickel oxide, or a mixture of these metal particles and oxide particles, or a composite hydroxide or composite oxide containing rhodium (Rh) and chromium (Cr) can be preferably used. More preferably, metal particles of platinum or ruthenium, or a composite hydroxide or composite oxide containing rhodium and chromium can be used.

[0035] A particularly suitable promoter includes rhodium-chromium oxide (RhCrOx). RhCrOx has high activity in hydrogen production by water reduction, but does not show activity in oxygen reduction. Therefore, it is possible to increase hydrogen production while suppressing the reverse reaction in which oxygen is reduced back to water, and is therefore effective in efficiently promoting the water splitting reaction.

[0036] The total amount of the promoter supported is preferably 0.01% by mass or more and 0.3% by mass or less based on the composite oxide particles. By increasing the amount supported to a certain extent, it is possible to fully exert the effect of promoting reduction and / or oxidation by the promoter. In addition, by restricting the amount supported to a certain extent, it is possible to prevent the active sites on the surface of the composite oxide particles from becoming insufficient.

[0037] The photocatalyst of this embodiment can be used for water decomposition reactions. When the photocatalyst in contact with water is irradiated with ultraviolet light, the water is decomposed to generate hydrogen and oxygen. Therefore, the photocatalyst contributes to the creation of clean energy. The photocatalyst of this embodiment can also be used as an environmental purification material. When the photocatalyst is irradiated with ultraviolet light, a strong oxidizing power is generated on its surface, and harmful substances such as organic compounds and bacteria in contact with it can be decomposed and removed.

[0038] <<2. Photocatalyst manufacturing method>> The photocatalyst manufacturing method of this embodiment is intended for manufacturing a photocatalyst having composite oxide particles containing ScVO4 as a main component compound. This manufacturing method includes a step of mixing a scandium (Sc) raw material and a vanadium (V) raw material to obtain a raw material mixture (raw material mixing step), a step of calcining the obtained raw material mixture at a temperature of 680°C or higher to obtain a reaction product (calcination step), and a step of heat-treating the obtained reaction product in a flux to obtain a heat-treated reaction product (heat treatment step). A step of washing the reaction product after the calcination step with an alkaline aqueous solution (alkali washing step) may be provided. Also, a step of washing the heat-treated reaction product after the heat treatment step with water (water washing step) may be provided. Furthermore, a step of supporting a co-catalyst on the heat-treated reaction product after the heat treatment step (co-catalyst supporting step) may be provided. Details of each step are described below.

[0039] <Raw material mixing process> In the raw material mixing step, a scandium (Sc) raw material and a vanadium (V) raw material are mixed to obtain a raw material mixture. As the scandium raw material, simple scandium or a scandium-containing compound can be used. Specific examples include, but are not limited to, metallic scandium (Sc) and scandium oxide (Sc2O3). Sc2O3 is readily available on the market as a powder. As the vanadium raw material, examples include, but are not limited to, vanadium oxide compounds such as ammonium metavanadate and vanadium oxide (V2O5). V2O5 is readily available on the market as a powder. In addition, the vanadium oxide compound decomposes in the subsequent calcination step and changes to V2O5.

[0040] The mixing ratio of the raw materials is not particularly limited as long as a photocatalyst containing ScVO4 as a main component compound can be obtained. However, it is preferable to mix the vanadium raw material in a slight excess.

[0041] Generally, the melting point of the scandium raw material is high, and the melting point of the vanadium raw material is low. For example, the melting point of Sc2O3 is 2485°C, while the melting point of V2O5 is 690°C. Therefore, in the subsequent firing process, the vanadium raw material (V2O5 powder, etc.) melts and diffuses into the particles of the scandium raw material (Sc2O3 powder, etc.), where it is thought that scandium vanadate (ScVO4, etc.) is formed. In this case, if the proportion of the vanadium raw material is too small, the penetration and diffusion into the scandium raw material particles may be insufficient, and the generation of ScVO4 may be inhibited. From the viewpoint of promoting the generation of ScVO4, it is preferable to mix the vanadium raw material in excess of the stoichiometric composition. In addition, the vanadium raw material mixed in excess also acts as a flux to improve the crystallinity of the generated ScVO4. It is expected that the improvement in the crystallinity of ScVO4 will lead to an improvement in the hydrogen generation amount and catalytic activity of the photocatalyst containing it.

[0042] The raw materials (scandium raw material, vanadium raw material) may be mixed by a known method. For example, a mixing device or a grinding and mixing device such as a mortar, a mortar mill, a Henschel mixer, a V-type mixer, a ball mill, an attritor, a bead mill, and / or a vibration mill may be used. The mixing may be performed in a dry or wet manner. However, since V2O5 has a high solubility in water, mixing in water may cause composition deviation or component segregation. Therefore, when V2O5 is used as the vanadium raw material and mixed in a wet manner, it is preferable to use a non-aqueous medium. In addition, when mixed in a wet manner, it is preferable to dry the resulting mixture.

[0043] <Firing process> In the calcination process, the resulting raw material mixture is calcined at a temperature of 680°C or higher to obtain a reaction product. As mentioned above, in the calcination process, the vanadium raw material melts and diffuses into the particles of the scandium raw material, where it forms scandium vanadate (ScVO4). In addition, when an excess amount of vanadium raw material is mixed, the excess vanadium raw material promotes the formation of ScVO4 and improves crystallinity.

[0044] The crystal structure of scandium vanadate formed during the sintering process depends on the sintering temperature. If the sintering temperature is below 680°C, the desired ScVO4 cannot be obtained, and the bixbyte-type ScVO4 is obtained. 3+x (x: 0-0.5) may be generated. From the viewpoint of promoting the generation of ScVO4 and improving crystallinity, it is preferable that the firing temperature is relatively high. On the other hand, if the firing temperature is excessively high, the vanadium raw material may volatilize, causing the composition of the final product to deviate, and the grain growth of the product may proceed excessively. In addition, a large amount of energy is required, and the deterioration of the equipment may progress, leading to an increase in production costs. The temperature for firing the raw material mixture is preferably 680°C or higher and 1300°C or lower.

[0045] When scandium oxide (Sc2O3) and vanadium oxide (V2O5) are used as the scandium raw material and the vanadium raw material, respectively, and calcined at a temperature of 680°C or higher, the reaction shown in the following formula (1) proceeds to the right.

[0046] Sc2O3+V2O5→ 2ScVO4 (1)

[0047] As long as the desired photocatalyst is obtained, the firing holding time is not limited. However, from the viewpoint of promoting the production of ScVO4 and improving the crystallinity, the firing holding time is preferably long to a certain extent. On the other hand, if the firing holding time is excessively long, the cycle time will be long, leading to an increase in manufacturing costs. The firing holding time is preferably 6 hours or more, and more preferably 8 hours or more and 15 hours or less. In addition, as long as the desired photocatalyst is obtained, the firing atmosphere is not limited. However, an oxygen-containing atmosphere such as air is preferable.

[0048] Furthermore, a flux, which will be described later, can be used in the firing process. In that case, synthesis conditions such as firing temperature and firing holding time are appropriately determined in consideration of particle growth of the reaction product.

[0049] The reaction product obtained in the firing step may be pulverized. Depending on the conditions of the firing step, the particle size of the reaction product may become excessively large, resulting in a decrease in photocatalytic activity. In such a case, it is preferable to subject the reaction product after the firing step to a pulverization treatment to reduce the particle size. The pulverization may be performed using a pulverizer such as a paint shaker, a ball mill, or a jet mill.

[0050] <Alkaline cleaning process> If necessary, a step of washing the reaction product obtained in the calcination step with an alkaline aqueous solution (alkali washing step) may be provided. By providing the alkali washing step, if the reaction product contains residual V2O5, this residual V2O5 can be removed, and as a result, a photocatalyst with even better stability in water can be obtained.

[0051] To explain this point, the reaction product obtained by mixing and firing powdered scandium raw material (e.g., Sc2O3 powder) and vanadium raw material (e.g., V2O5 powder) is composed of micron-sized particles with a particle size of 1 μm or more. In addition, submicron-sized particles may adhere to the surface of these micron-sized particles. These submicron-sized particles are presumed to be made of V2O5. In particular, when an excess amount of vanadium raw material is mixed in order to promote the production of ScVO4 and improve crystallinity, the excess vanadium raw material tends to remain in the reaction product (photocatalyst) as V2O5 after the firing process.

[0052] On the other hand, as mentioned above, vanadium oxide (V2O5) has poor stability in water. Therefore, a photocatalyst containing residual V2O5 may lose stability when applied to water splitting. Therefore, if residual V2O5 is present in the reaction product, it is desirable to remove it as much as possible. In this regard, V2O5 can be easily removed with an alkaline aqueous solution. Therefore, by subjecting the reaction product to alkaline washing using an alkaline aqueous solution, the residual V2O5 can be efficiently removed, resulting in a photocatalyst with excellent stability in water.

[0053] The alkaline aqueous solution used in the alkaline cleaning is not particularly limited as long as it can dissolve and remove vanadium oxide (V2O5). For example, aqueous solutions containing sodium hydroxide (NaOH), potassium hydroxide (KOH), calcium hydroxide (Ca(OH)2), sodium carbonate (Na2CO3), ammonia (NH3), and sodium bicarbonate (NaHCO3) can be used. The concentration of the aqueous solution is also not particularly limited as long as it can dissolve and remove V2O5. For example, when an NaOH aqueous solution is used, the concentration is preferably 0.01M or more. In addition, during the alkaline cleaning, an alkaline aqueous solution at room temperature or a heated alkaline aqueous solution may be used.

[0054] After the alkali washing, the reaction product is preferably washed with water to remove the alkaline components, and the reaction product is preferably dried after the water washing.

[0055] <Heat treatment process> In the heat treatment process, the reaction product obtained through the calcination process is heat-treated in a flux to obtain a heat-treated reaction product. Heat treatment in a flux improves the crystallinity of the reaction product, including ScVO4. Specifically, defects on the surface of the reaction product particles that have insufficient catalytic activity are filled in, or the crystallinity of the regular arrangement of atoms that make up the reaction product is improved. As a result, the catalytic activity of the heat-treated reaction product (photocatalyst) obtained is significantly improved.

[0056] Heat treatment is particularly effective when the reaction product after the calcination process is pulverized. The impact of the pulverization process reduces the particle size of the pulverized material. The impact of the pulverization process damages the particle crystals, causing distortions and defects in the lattice. By subjecting such damaged crystals to heat treatment in a flux, the crystallinity of the pulverized material is improved, resulting in improved catalytic activity.

[0057] The flux is not particularly limited as long as it is a component that melts in the heat treatment process and has the effect of enhancing the photocatalytic activity of the reaction product. However, it is preferable to use one or more components selected from the group consisting of chlorides, carbonates, and hydroxides of alkali metal elements such as lithium (Li), sodium (Na), and potassium (K), and vanadium oxide (V2O5). These components are highly soluble in water. Therefore, the flux can be easily separated and removed by washing the reaction product to be heat-treated after the heat treatment process with water. In addition, one type of flux may be used alone, or multiple types of fluxes may be used in combination. However, from the viewpoint of economy, it is particularly preferable that the flux is a mixture of sodium chloride (NaCl) and potassium chloride (KCl).

[0058] The heat treatment temperature in the heat treatment step is not limited as long as it is a temperature at which the flux melts. However, it is preferably 640°C or more and 850°C or less. When a flux consisting of a mixture of NaCl and KCl is used, it is preferably 700°C or more. The heat treatment time is preferably 1 hour or more and 24 hours or less. By setting the heat treatment time to 1 hour or more, the effect of improving the crystallinity of ScVO4 in the reaction product can be fully exerted. On the other hand, by setting the heat treatment time to 24 hours or less, the decomposition and grain growth of ScVO4 during the heat treatment step can be suppressed. If the heat treatment is performed under such conditions, the particle size of the reaction product before the heat treatment and the heat-treated reaction product after the heat treatment are almost the same.

[0059] By the way, it is also possible to use the above-mentioned flux in the calcination process. ScVO4 can be synthesized by reacting the starting materials, Sc2O3 as a scandium source and V2O5 as a vanadium source, in the flux during calcination. When a mixture of KCl and NaCl is used as the flux, the product obtained by the synthesis method has ScVO4 as the main phase, but the Sc2O3 phase is also confirmed. In particular, when the calcination time is 12 hours, the higher the calcination temperature, the more Sc2O3 phase is confirmed. Furthermore, when the reaction product is observed with an SEM, irregular ScVO4 particles with a size of over 10 μm are sometimes confirmed. It is believed that such irregular particles have grown into particles in the flux. The catalytic activity of reaction products of such sizes is poor.

[0060] However, it may be possible to synthesize small ScVO4 particles by optimizing synthesis conditions such as the sintering temperature and time.

[0061] In addition, a reaction product with improved crystallinity can be obtained by subjecting the main phase ScVO4 to grain growth in the flux, and the reaction product can be pulverized as described above to a particle size suitable for use as a photocatalyst. The heat treatment process of this embodiment can then be carried out to improve the crystallinity of the surface of the pulverized particles, thereby obtaining a photocatalyst.

[0062] In other words, the heat treatment process of this embodiment can easily improve the particle surface of the reaction product obtained in the calcination process, which has insufficient catalytic activity, or the particle surface of the pulverized reaction product that has grown to an inappropriate particle size in the calcination process.

[0063] <Water washing process> If necessary, the reaction product to be heat-treated may be washed with water. Fluxes such as chlorides of alkali metal elements can be removed by washing with water. In addition, when ScVO4 is decomposed in the heat treatment process to produce V2O5, the produced V2O5 can be removed. In washing with water, the reaction product to be heat-treated may be put into ion-exchanged water, stirred, and then filtered. The temperature of the ion-exchanged water during washing is preferably 20°C or higher and 100°C or lower. For filtration, reduced pressure filtration using a membrane filter or the like may also be used. After filtration, reduced pressure drying may be performed using a vacuum dryer or the like. The temperature of the reduced pressure atmosphere is preferably 20°C or higher and 100°C or lower, and the drying time is preferably 6 hours or longer.

[0064] <Co-catalyst supporting process> If necessary, a co-catalyst may be supported on the heat-treated reaction product. The co-catalyst may be supported by a known method such as an impregnation method or a photoelectrodeposition method. The impregnation method is a method in which a solution containing a co-catalyst raw material such as a metal salt is mixed with main catalyst particles, and then the mixture is dried and heat-treated to support the co-catalyst. The photoelectrodeposition method is a method in which a solution containing a co-catalyst raw material is stirred with main catalyst particles, and light is irradiated to support the co-catalyst.

[0065] When a promoter made of rhodium-chromium oxide (RhCrOx) is supported by the impregnation method, for example, an aqueous solution containing a Rh raw material and a Cr raw material is added to and mixed with the heat-treated reaction product, followed by drying, and the resulting dried product is calcined in an oxygen-containing atmosphere. Examples of Rh raw materials include, but are not limited to, sodium hexachlororhodate (III) and its hydrates. Examples of Cr raw materials include, but are not limited to, chromium nitrate and its hydrates. Calcination may be performed in an oxygen-containing atmosphere such as air at a temperature of 300°C to 400°C.

[0066] In this manner, the photocatalyst of this embodiment can be obtained. The photocatalyst of this embodiment is particularly useful for the decomposition reaction of water and the decomposition and removal of harmful substances.

[0067] <<3. Water splitting method>> In the water splitting method of the present embodiment, a suspension containing the above-mentioned photocatalyst and water is irradiated with ultraviolet light, thereby splitting the water to generate hydrogen and oxygen. Specifically, the photocatalyst and water are mixed to prepare a suspension. Then, the obtained suspension is irradiated with ultraviolet light.

[0068] It is preferable to use a light source of ultraviolet light to be irradiated that has sufficient intensity in the wavelength region of 300 nm or more and 500 nm or less. The ultraviolet light irradiation causes a water decomposition reaction on the surface of the photocatalyst in the suspension, generating hydrogen and oxygen. The ultraviolet light irradiation may be performed by placing the suspension in a closed circulation system. The suspension may also be stirred during irradiation. EXAMPLES

[0069] The present embodiment will be described in more detail with reference to the following examples, but the present invention is not limited to the following examples.

[0070] (1) Evaluation of photocatalysts Using the photocatalyst (composite oxide particles) as a sample, various characteristics were evaluated as follows.

[0071] <xrd> The sample was analyzed by powder X-ray diffraction (XRD) to identify the crystal phase. The XRD analysis was performed under the following conditions.

[0072] - X-ray diffractometer: Rigaku Corporation, Mini Flex - Radiation source: CuKα - Tube voltage: 30 kV - Tube current: 10 mA - Scanning speed: 1.25° / min - Scanning range (2θ): 15 - 60°

[0073] <SEM Observation> The secondary electron image of the sample was obtained using a scanning electron microscope (SEM; Carl Zeiss, ULTRA55) to examine the shape of the sample particles.

[0074] <Photocatalytic Performance for Water Splitting> A photocatalytic performance test for water splitting was conducted by irradiating the sample with ultraviolet (UV) light in a gas-closed circulation system. Specifically, 0.1 g of the sample was added to 100 ml of distilled water, and then ultrasonic dispersion was performed for 30 seconds to prepare a suspension. The prepared suspension was placed in a reaction vessel, and the reaction vessel was placed in the closed circulation system. After sufficiently removing the dissolved gas in the suspension and degassing the closed circulation system, argon (Ar) gas was enclosed in the closed circulation system, and the pressure inside the system was maintained at 10 kPa. Next, the photocatalytic performance was evaluated using a 300 W xenon lamp equipped with a half mirror CM2 that reflects only UV light with a wavelength of 300 - 500 nm. At that time, in order to prevent heating of the suspension due to light irradiation, the periphery of the reaction vessel was cooled with cooling water set at 15°C, and while continuously stirring the suspension, the gas generated by the photocatalytic reaction was analyzed and the generation amount was measured. The analysis and measurement of the generated gas were performed using a gas chromatograph (Shimadzu Corporation, GC-8A) equipped with a column using molecular sieve 5A as a packing agent and a TCD (Thermal Conductivity Detector) detector.

[0075] (2) Synthesis of ScVO4 Composite Oxide Particles by Solid-State Reaction Method [Experimental Example 1 (Reference Example)] In Experimental Example 1, composite oxide particles were synthesized by a solid-phase reaction method and evaluated. Specifically, scandium oxide (Sc2O3) powder (Sumitomo Metal Mining Co., Ltd., purity 99.99%) and vanadium oxide (V2O5) powder (Wako Pure Chemical Industries, Ltd., special grade, purity 99%) were weighed out so as to obtain 0.03 moles of ScVO4. At this time, the raw materials (Sc2O3 powder, V2O5 powder) were weighed out so that the molar ratio (atomic ratio) of the charged composition was V / Sc=1.00. The weighed raw materials were then mixed in an agate mortar for 30 minutes to prepare a raw material mixture.

[0076] Next, the obtained raw material mixture was placed in an alumina crucible and fired in air at 650°C, 800°C, 960°C, or 1000°C for 12 hours. At this time, the heating rate to each firing temperature was 10°C per minute. In this manner, a reaction product (fired product) consisting of 0.03 mol of composite oxide particles was produced for each firing temperature.

[0077] Each reaction product according to Experimental Example 1 was evaluated by an X-ray diffractometer. The XRD spectrum of each reaction product at 2θ=15 to 60° is shown in Figure 1. For reference, Figure 1 also shows the standard diffraction peaks of Sc2O3 (JCPDS card 01-084-1880), V2O5 (JCPDS card 00-041-1426), and ScVO4 (JCPDS card 01-079-7028; ScVO4, I41 / amd, tetragonal).

[0078] In the reaction product sintered at 650°C, phases based on unreacted raw materials (Sc2O3, V2O5) were confirmed, and almost no ScVO4 was produced. This result indicates that the ScVO4 synthesis reaction does not proceed when sintered below the melting point of V2O5 (690°C). In contrast, in the reaction product sintered at temperatures above 800°C, the diffraction peaks in the XRD spectrum almost coincided with the standard diffraction peaks of tetragonal ScVO4. It was found that a single-phase ScVO4 reaction product can be obtained by increasing the sintering temperature to above 800°C.

[0079] The reaction products from firing at 800°C and 960°C were washed with 60°C ion-exchanged water, filtered, and then left for one day in a reduced pressure atmosphere at 40°C to obtain the washed reaction products. SEM images of the reaction products before and after washing are shown in Figure 2.

[0080] (3) Synthesis of ScVO4 composite oxide particles in flux [Experimental Example 2 (Reference Example)] In Experimental Example 2, composite oxide particles were prepared by a flux method in which they were fired in a flux, and the evaluation was performed. Specifically, scandium oxide (Sc2O3) powder (Sumitomo Metal Mining Co., Ltd., purity 99.99%) and vanadium oxide (V2O5) powder (Wako Pure Chemical Industries, Ltd., special grade, purity 99%) were weighed out so as to obtain 0.01 mol of ScVO4. At this time, the raw materials (Sc2O3 powder, V2O5 powder) were weighed out so that the molar ratio (atomic ratio) of the charged composition was V / Sc=1.00. Next, the weighed raw materials were mixed in an agate mortar for 25 minutes to prepare a raw material mixture. Then, 0.05 mol of NaCl and 0.05 mol of KCl were added to the obtained raw material mixture, and the mixture was further mixed in the agate mortar for 10 minutes to obtain a mixture.

[0081] The resulting mixture was then placed in an alumina crucible and fired in air at 650°C, 700°C, 750°C, or 800°C for 12 hours. The heating rate to each firing temperature was 10°C per minute. In this manner, 0.01 mol of fired product was produced for each firing temperature.

[0082] After calcination, the obtained calcined product was washed by stirring for 40 minutes in ion-exchanged water at 60°C. At this time, the rotation speed during stirring was 450 rpm. Next, the washed calcined product was filtered under reduced pressure using a membrane filter, and further dried for one day under reduced pressure using a vacuum dryer at a temperature of 40°C to obtain a reaction product.

[0083] An X-ray diffractometer was used to evaluate each reaction product in Experimental Example 2. The XRD spectrum of each reaction product at 2θ=15 to 60° is shown in FIG.

[0084] The standard diffraction peaks of tetragonal ScVO4 (JCPDS card 01-079-7028; ScVO4, I41 / amd, tetragonal) were confirmed at all firing temperatures of 650°C, 700°C, 750°C, and 800°C. Therefore, the main phase was determined to be ScVO4. It was also confirmed that the amount of Sc2O3 increased with increasing firing temperature.

[0085] FIG. 4 shows SEM images of the reaction products of Experimental Example 2. The reaction products were particles with a particle size exceeding 10 μm. The reaction products of Experimental Example 2 had a larger particle size than the reaction products of Experimental Example 1.

[0086] (4) Improving catalytic activity by flux treatment of reaction products (heat treatment process) [Experimental Example 3 (Example)] The reaction product (800°C calcined product) obtained in Experimental Example 1 was further subjected to flux treatment. Specifically, 0.05 mol of NaCl and 0.05 mol of KCl were weighed out and mixed in an agate mortar for 20 minutes to obtain a mixed chloride. 0.01 mol of the reaction product (800°C calcined product) from Experimental Example 1 was added to the mixed chloride, and further mixed in an agate mortar for 10 minutes to obtain a mixture.

[0087] The resulting mixture was then placed in an alumina crucible and heat-treated in air at 750°C for 12 hours. The resulting product was washed by stirring in ion-exchanged water at 60°C for 40 minutes. The stirring speed was 450 rpm. The washed product was filtered under reduced pressure using a membrane filter, and further dried for one day under reduced pressure using a vacuum dryer at 40°C to obtain a heat-treated reaction product.

[0088] The heat-treated reaction product of Experimental Example 3 was evaluated by an X-ray diffractometer. The XRD spectrum of the heat-treated reaction product at 2θ=15 to 60° is shown in Figure 5. Note that Figure 5 also shows, as reference data, the XRD spectra of the reaction product of Experimental Example 1 (calcination temperatures of 800°C and 960°C) and the reaction product of Experimental Example 2 (calcination temperature of 750°C).

[0089] No Sc2O3 peak was observed in the XRD spectrum of the reaction product before heat treatment (Experimental Example 1, firing temperature 800°C), whereas a Sc2O3 peak was observed in the XRD spectrum of the heat-treated reaction product after heat treatment (Experimental Example 3).

[0090] SEM images of the reaction product before heat treatment (Experimental Example 1, firing temperature 800°C) and the reaction product after heat treatment (Experimental Example 3) are shown in Figures 6A and 6B, respectively. The particle sizes of both were almost the same.

[0091] The reaction product before heat treatment (Experimental Example 1, calcination temperature 800°C) and the heat-treated reaction product after heat treatment (Experimental Example 3) were loaded with RhCr oxide (RhCrOx) as a promoter by impregnation. At that time, the promoter was loaded so that the rhodium amount and chromium amount were 0.1 mass% for each of the reaction product and the heat-treated reaction product.

[0092] The specific procedure for supporting the co-catalyst was as follows. First, 0.25 g of the reaction product or the reaction product to be heat-treated and 1.44 mg of sodium hexachlororhodate (III) n-hydrate (Na3[RhCl6]·nH2O, containing 17.4 mass% Rh) were weighed on a watch glass. Then, 1.44 mg of sodium hexachlororhodate (III) n-hydrate was added to the weighed amount. -2 478μL of 1.2mol / L chromium nitrate nonahydrate (Cr(NO3)3·9H2O) aqueous solution and 2.5mL of ion-exchanged water were added. The resulting mixture was subjected to ultrasonic mixing for 1 minute, and then stirred with a glass rod in a thermostatic water bath at 70℃ to remove the solvent and obtain a dried product. The dried product was then placed in a crucible and fired in air at 350℃ for 1 hour. Through this series of operations, the RhCr oxide promoter was supported on the reaction product or the heat-treated reaction product.

[0093] The reaction product after supporting the co-catalyst (Experimental Example 1, calcined at 800°C) and the heat-treated reaction product (Experimental Example 3) were evaluated for their water-splitting photocatalytic performance. The evaluation results are shown in Figures 7A and 7B, respectively. The heat-treated reaction product after heat treatment (Experimental Example 3) generated more hydrogen than the reaction product before heat treatment (Experimental Example 1, calcined at 800°C).

[0094] The above results show that, according to this embodiment, the water splitting photocatalytic activity of the reaction product (ScVO4 photocatalyst particles) synthesized in the firing process is improved by undergoing a heat treatment process (heat treatment using flux).< / xrd>

Claims

1. ScVO 4 A method for producing a photocatalyst comprising composite oxide particles containing as a main component compound, mixing a scandium (Sc) raw material and a vanadium (V) raw material to obtain a raw material mixture; calcining the raw material mixture at a temperature of 680° C. or higher to obtain a reaction product; and heat treating the reaction product in a flux to obtain a heat-treated reaction product.

2. The flux contains chlorides, carbonates, and hydroxides of alkali metal elements, and vanadium oxide (V 2 O 5 2. The method according to claim 1, wherein the compound is one or more selected from the group consisting of:

3. The method of claim 2 , wherein the flux is a mixture of sodium chloride (NaCl) and potassium chloride (KCl).

4. A photocatalyst obtained by the method according to any one of claims 1 to 3.

5. A method for decomposing water, comprising irradiating a suspension containing the photocatalyst according to claim 4 and water with ultraviolet light, thereby decomposing the water to generate hydrogen and oxygen.

Citation Information

Patent Citations

  • Paper holder with slider

    JP2020040830A

  • Composite photocatalyst, and photocatalyst material

    WO2014046305A1